STUDY OF PARTICLE BOARDS CHARACTERISTIC BASED ON SENGON WOOD PARTICLE AND OIL PALM EMPTY FRUIT BUNCHES - Sunardi, Sunardi; Putra, Rizky Kurnia; Lusiani, Rina; Saefuloh, Iman; Sudrajad, Agung (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
Oil palm empty fruit bunches (OPEFB) as a by-product of the palm oil processing industry. This waste can cause problems for the environment and human health. Utilization of OPEFB waste as particle board material to reduce this waste. The composition of the particle board is based on volume fraction, namely 15% empty palm fruit fiber, 15% epoxy resin, 20% PVAc adessive, and 50% sawdust. The manufacturing process of samples was carried out using the single punch cold press method with compaction pressure of 10, 30, and 50 bar. The experimental results show that a compacting pressure of 10 bar can produce particle board performance according to SNI 03-2105-2006 with a characteristic density of 0.93 gram/cm3, thickness swelling of 2.52%, hardness of 24 N/mm2, flexural strength of 840.05 N/mm2, and impact strength 6.00 kJ/m2.